The Cognitive Aging of Episodic Memory: A View Based on the Event-Related Brain Potential - Friedman, David (Frontiers in Behavioral Neuroscience, 2013)
A cardinal feature of older-adult cognition is a decline, relative to the young, in the encoding and retrieval of personally-relevant events, i.e. episodic memory (EM). A consensus holds that familiarity, a relatively automatic feeling of knowing that can support recognition-memory judgments, is preserved with aging. By contrast, recollection, which requires the effortful, strategic recovery of contextual detail, declines as we age. Over the last decade, ERPs have become increasingly important tools in the study of the aging of EM, because a few, well-researched EM effects have been associated with the cognitive processes thought to underlie successful EM performance. EM effects are operationalized by subtracting the ERPs elicited by correctly-rejected, new items from those to correctly recognized, old items. Although highly controversial, the mid-frontal effect (a positive component between 300 and 500 ms, maximal at fronto-central scalp sites) is thought to reflect familiarity-based recognition. A positivity between 500 and 800 ms, maximal at left-parietal scalp, has been labeled the left-parietal EM effect. A wealth of evidence suggests that this brain activity reflects recollection-based retrieval. Here, I review the ERP evidence in support of the hypothesis that familiarity is maintained while recollection is compromised in older relative to young adults. I consider the possibility that the inconsistency in findings may be due to individual differences in performance, executive function and quality of life indices, such as socio-economic status.